ENHANCED SECURITY MECHANISM IN CLOUD COMPUTING: A REVIEW - Kaur, Gagandeep; Garg, Dr. Mohita; Jyoti, Mrs. Navjot (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2015)
Cloud is a term used as a metaphor for the wide area networks (like internet) or any such large networked environment. It came partly from the cloud-like symbol used to represent the complexities of the networks in the schematic diagrams. It represents all the complexities of the network which may include everything from cables, routers, servers, data centers and all such other devices. Cloud based systems saves data off multiple organizations on shared hardware systems. Data segregation is done by encrypting data of users, but encryption is not complete solution. We can do segregate data by creating virtual partitions of data for saving and allowing user to access data in his partition only. We will be implementing cloud security aspects for data mining by implementing cloud system. After implementing cloud infrastructure for data mining for cloud system we shall be evaluating security measure for data mining in cloud. We will be fixing threats in data mining to Personal/private data in cloud systems.Â Â 